2-Propyl-N′-[1,7,7-trimethylbicyclo[2.2.1]hept-2-ylidene]pentanehydrazide - Mariia Nesterkina; Dmytro Barbalat; Ildar Rakipov; Iryna Kravchenko (Molbank, 2020)
2-Propyl-N′-[1,7,7-trimethylbicyclo[2.2.1]hept-2-ylidene]pentanehydrazide was obtained in 80% yield via the Einhorn variation of the Schotten–Baumann method by (+)-camphor hydrazide condensation with valproic acid (VPA) chloride. The structure of the titled compound was verified by Raman, FTIR, 1H-NMR, and 13C-NMR spectral analysis along with FAB-mass spectrometry. Thermal properties of synthesized derivative were elucidated by DSC and its purity by HPLC. The compound was successfully tested as a potential anticonvulsant agent based on models of chemically- and electrically-induced seizures.